Cloning and heterologous expression of Os-AP2/ERF-N22 drought inducible rice transcription factor in E. coli - KUMAR, VAIBHAV; ALI, KISHWAR; KUMAR, AMRESH; TEWARI, KALPANA; GARG, NITIN KUMAR; CHANGAN, SUSHIL S; TYAGI, ARUNA (The Indian Journal of Agricultural Sciences, 2018)
AP2/ERF a plant specific transcription factor plays a crucial role in the expression and regulation of abiotic stress related genes. In this study, we have characterized a rice transcription factor named Os-AP2/ERF-N22. It contains single AP2 domain which spans from 5th to 70th amino acid residue in the protein which is 243 amino acid residue long. The partial sequence of the gene encoding Os-AP2/ERF transcription factor was amplified and cloned into pET29a bacterial expression vector. The histidine-tagged truncated Os-AP2/ERF-N22 protein was expressed in BL21(DE3) strain of E. coli after induction with 0.5mM IPTG. A time course induction study was used to optimize the protein expression and the recombinant Os-AP2/ERF-N22 was purified using Ni-NTA agarose column chromatography. The 26.74 kDa recombinant Os-AP2/ERF-N22 was visualized using SDS-PAGE analysis and its expression was further confirmed by western blot analysis using anti-his primary antibody and alkaline phosphatase conjugated secondary antibody. Antibody against the purified truncated AP2/ERF-N22 was custom synthesized and it was used to quantitate the expression of Os-AP2/ERF-N22 transcription factor in rice at the protein level.